Ethical and strategic challenges of AI weapons: A call for global action - Bai, Junwen; Mujumdar, Arun S.; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2024)
The intelligence of AI weapons is primarily reflected in their ability to make autonomous decisions. However, the autonomy granted to these weapons systems raises deep ethical concerns. The very concept of autonomy, originating from the Greek for "self-law," hints at machines making pivotal decisions without human guidance. Despite AI weapons' capability to execute complex computations and decision-making processes, they are still limited by their programming code. It’s difficult to make the 'black box' nature of machine learning fully interpretable or to ensure that AI systems perform as expected after deployment. These systems learn from their environment, and the real world is never as simple as the laboratory. This absence of human moral judgment is troubling and poses risks of tragic errors.Keywords: ethical challenges, strategic challenges, AI weapons, global actionDOI: 10.25165/j.ijabe.20241705.9456Citation: Bai J W, Mujumdar A S, Xiao H W. Ethical and strategic challenges of AI weapons: A call for global action. Int J Agric & Biol Eng, 2024; 17(5): 293-294.